2019
DOI: 10.1089/dia.2018.0384
|View full text |Cite|
|
Sign up to set email alerts
|

State of Type 1 Diabetes Management and Outcomes from the T1D Exchange in 2016–2018

Abstract: Objective: To provide a snapshot of the profile of adults and youth with type 1 diabetes (T1D) in the United States and assessment of longitudinal changes in T1D management and clinical outcomes in the T1D Exchange registry. Research Design and Methods: Data on diabetes management and outcomes from 22,697 registry participants (age 1-93 years) were collected between 2016 and 2018 and compared with data collected in 2010-2012 for 25,529 registry participants. Results: Mean HbA1c in 2016-2018 increased from 65 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

69
1,338
19
28

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 1,519 publications
(1,454 citation statements)
references
References 19 publications
69
1,338
19
28
Order By: Relevance
“…The use of CGM increased from 6% of people with diabetes in 2012 to 38% in 2017. In children, the use of insulin pump therapy rose to 63% ; however, despite the wide adoption of new technologies, longitudinal real‐world data from the type 1 registry showed that HbA 1c values rose from 61.7 mmol/mol to 68.3 mmol/mol during this period. This might indicate that technology alone is not a remedy for poor glycaemic control.…”
Section: What Has the Past 25 Years Of Research Told Us?mentioning
confidence: 99%
“…The use of CGM increased from 6% of people with diabetes in 2012 to 38% in 2017. In children, the use of insulin pump therapy rose to 63% ; however, despite the wide adoption of new technologies, longitudinal real‐world data from the type 1 registry showed that HbA 1c values rose from 61.7 mmol/mol to 68.3 mmol/mol during this period. This might indicate that technology alone is not a remedy for poor glycaemic control.…”
Section: What Has the Past 25 Years Of Research Told Us?mentioning
confidence: 99%
“…These concerns continue to this day with an average hemoglobin A1C (HbA1c) >8% in children 8 and above, reaching 9% by 16 years of age . Less than 20% of youth achieve HbA1c levels in target range per current American Diabetes Association guidelines (HbA1c ≤7.5%) . In addition, about 10% suffer from one or more episodes of diabetes ketoacidosis (DKA) per year and 6% have one or more severe hypoglycemic events per year …”
Section: Introductionmentioning
confidence: 99%
“…Despite the advantages of CGM systems, their adoption has been slow to grow, increasing from only 9% in 2014 to 38% in 2018 . Their use is even lower among individuals with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%